2022
DOI: 10.1007/s40290-021-00413-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Medical Affairs Pharmaceutical Physician Value (MAPPval) Instrument

Abstract: Background A pilot study conducted in 2020 suggested that Medical Affairs Pharmaceutical Physicians (MAPPs) may be inherently undervalued within the pharmaceutical industry and vulnerable to replacement by less qualified roles. There are currently no standardized metrics to measure MAPP performance, thus it is necessary to measure the value of MAPPs to employers and clarify the need for their specific skills. Objectives The first aim of this study was to identify a list of indicators to produce an MAPP value m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Items of the medical affairs definition could be categorised into four previously defined MAPP functions ( Table 2 ) ( Jandhyala, 2022 ). Content analysis showed that the consensus-generated definition varied from previous definitions in four key ways: the designation of medical affairs as a medical specialty, the leadership of medical affairs in medicine adoption, the generation of real-world evidence and the specification of distinct stakeholders who benefit from medical affairs ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Items of the medical affairs definition could be categorised into four previously defined MAPP functions ( Table 2 ) ( Jandhyala, 2022 ). Content analysis showed that the consensus-generated definition varied from previous definitions in four key ways: the designation of medical affairs as a medical specialty, the leadership of medical affairs in medicine adoption, the generation of real-world evidence and the specification of distinct stakeholders who benefit from medical affairs ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the definition was robustly supported by consensus. All items could be categorised into four previously defined MAPP functions: protecting patients’ interests, medicine adoption and regulation, evidence generation and gatekeeper stakeholder engagement ( Jandhyala, 2022 ), which provided confidence in the reliability and validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations